Effect of Education Level and Job Placement on Employee Work Productivity at Regional Drinking Water Company Tirta Bhagasasi Rawa Lumbu Bekasi Branch - Safira, Meidiana Eka; Marginingsih, Ria (Bina Bangsa International Journal of Business and Management, 2022)
The purpose of the study was to determine the Effect of Education Level and Job Placement on Employee Work Productivity at the Tirta Bhagasasi Regional Drinking Water Company (PDAM) Rawa Lumbu Bekasi Branch. This research uses quantitative methods. The sampling technique used is a  saturated sampling technique (census). The sample used was 42 people. data collection techniques by conducting interviews, observations, and dissemination of questionnaires. For data analysis using PLS (Partial Least Square), PLS is one of the variant-based SEM statistical methods designed to solve multiple regressions when there are specific problems with the calculated data using the SmartPLS 3.3.3 program